Trends in referrals to liaison psychiatry teams from UK emergency departments for patients over 65. (29th April 2021) - Crowther, George; Chinnasamy, Manimegalai; Bradbury, Sarah; Shaw, Laura; Ormerod, Sara; Wilkinson, Alison; Chubb, Rebecca; Daher, Mazen; Kumar, Pramod; Gaskin, Andrew; Williams, Karen; Brennan‐Tovey, Justine; et al.
Abstract: Introduction: The number of people over the age of 65 attending Emergency Departments (ED) in the United Kingdom (UK) is increasing. Those who attend with a mental health related problem may be referred to liaison psychiatry for assessment. Improving responsiveness and integration of liaison psychiatry in general hospital settings is a national priority. To do this psychiatry teams must be adequately resourced and organised. However, it is unknown how trends in the number and type referrals of older people to liaison psychiatry teams by EDs are changing, making this difficult. Methods: We performed a national multi‐centre retrospective service evaluation, analysing existing psychiatry referral data from EDs of people over 65. We described trends in the number, rate, age, mental health presentation, and time taken to assessment over a 7 years period. Results: Referral data from 28 EDs across England and Scotland were analysed ( n = 18, 828 referrals). There was a general trend towards increasing numbers of people referred to liaison psychiatry year on year. Variability in referral numbers between different departments, ranged from 0.1 to 24.3 per 1000 ED attendances. The most common reasons for referral were mood disorders, self‐harm and suicidal ideas. The majority of referrals were assessed within 60 min, however there is variability between departments, some recording waits over 11 h. Discussion: The data suggests great inter‐departmental variability in referral numbers. Is not possible to establish the cause of variability. However, the data highlights the importance of asking further questions about why the differences exist, and the impact that has on patient care. Key points: There is a general trend towards increasing numbers of people over the age of 65 referred to liaison psychiatry from Emergency Departments (EDs) There is variability in the number of people over the age of 65 referred from UK EDs from hospital to hospital The most common reasons for the referral of people over the age of 65 to liaison psychiatry by the emergency department are mood disorders, self‐harm and suicidal ideas